MENINGKATKAN KEMAMPUAN MENGENAL KONSEP BILANGAN 1-10 MELALUI PERMAINAN BOWLING PLASTIK BAGI ANAK TUNARUNGU RINGAN - Ginting - Fitryani (Jurnal Penelitian Pendidikan Khusus, 2012)
This research background light by deaf children who are not familiar with the concept of number 1-10. Based on this study aims to introduce the concept of numbers 1-10 correctly and see if the plastic bowling games can improve children's ability to recognize the concept of number 1-10.This research uses experimental research is in the form of Single Subject Research (SSR) with AB designs. The research was first seen from the baseline condition, after that proceed on the condition of Intervention. The data obtained were processed by the graphics.The results of this study indicate that children's ability to recognize the concept of numbers 1-10 can be increased through plastic bowling game. Performed at baseline conditions in the five-time observation of children's ability to recognize the concept of numbers as much as 0% -10%, the intervention conditions increased the ability of the child is a child could recognize the concept of number as many as 10% -100%.